Management of intersections with multi-modal high-resolution data. (July 2016) - Muralidharan, Ajith; Coogan, Samuel; Flores, Christopher; Varaiya, Pravin
Highlights: Records lane, speed, signal phase and time vehicles enter intersection; and pedestrians enter crosswalk. Processes data to provide vehicle turn counts, waiting times, Purdue Coordination Diagram, and Improved timing plans. Estimates red light, speed, and right-turn-on-red (RTOR) violations, and vehicle–vehicle pedestrian–vehicle conflicts. Abstract: A high-resolution (HR) data system for an intersection collects the location (lane), speed, and turn movement of every vehicle as it enters an intersection, together with the signal phase. Some systems also provide video monitoring; others measure pedestrian and bicycle movements; and some have vehicle to infrastructure (V2I) communication capability. The data are available in real time and archived. Real time data are used to implement signal control. Archived data are used to evaluate intersection, corridor, and network performance. The system operates 24 × 7 . Uses of a HR data system for assessing intersection performance and improving mobility and safety are discussed. Mobility applications include evaluation of intersection performance, and the design of better signal control. Safety applications include estimates of dilemma zones, red-light violations, and pedestrian–vehicle conflicts.